2006
DOI: 10.2151/jmsj.84.199
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Baiu Frontal Activity in the Future Climate Simulated by Super-High-Resolution Global and Cloud-Resolving Regional Climate Models

Abstract: Changes in the Baiu frontal activity in the future climate are examined, making use of super-highresolution global and cloud-resolving regional climate models (20-km-mesh AGCM and 5-km-mesh NHM). In the present study, the focus is on the lengthened duration of the Baiu, and the characteristics of the precipitation during the Baiu season in the future climate.First, 10-year global-scale simulations of the present, and future climates are conducted by the 20-km-mesh AGCM. The present climate simulation accuratel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Our results are consistent with theirs. The study by Yasunaga et al (2006), with a non-hydrostatic 5-km-mesh re- gional model, has also indicated the delay in the withdrawal date of the Baiu season. Our result is consistent with the results above.…”
Section: Precipitationmentioning
confidence: 97%
See 1 more Smart Citation
“…Our results are consistent with theirs. The study by Yasunaga et al (2006), with a non-hydrostatic 5-km-mesh re- gional model, has also indicated the delay in the withdrawal date of the Baiu season. Our result is consistent with the results above.…”
Section: Precipitationmentioning
confidence: 97%
“…1d). Yasunaga et al (2006) attributed the intensification and stagnation of the Ogasawara high in the future climate, to the concentration of active convection over this equatorial higher SST region. This higher-SST region might lock the position of the Ogasawara high, and hinder the high from moving northward.…”
Section: Precipitationmentioning
confidence: 99%
“…Mizuta et al (2006) conducted a numerical simulation using a GCM with a 20 km mesh called MRI-GCM TL959L60 that was developed by the Meteorological Research Institute, Japan Meteoro logical Agency (hereafter, MRI-GCM). The simulation yielded a significantly improved representation of precipitation including specific phenomena such as the Baiu (Yasunaga et al 2006;Kusunoki et al 2006), the Asian monsoon (Yatagai et al 2005;Mizuta et al 2006), and the tropical cyclone . Mizuta et al (2006) also indicated that the model performance (e.g., the global distribution of precipitation and surface temperature) was drastically improved by the MRI-GCM, which can simulate local wind circulation.…”
mentioning
confidence: 99%
“…Therefore, the projection of climate changes in such Baiu frontal precipitation with 5km-NHM is an important challenge. Several results of this experiment have already been published Hashimoto et al 2005;Kanada et al 2005;Wakazuki et al 2005;Yasunaga et al 2005;Yasunaga et al 2006;Nakamura et al 2008).…”
Section: Introductionmentioning
confidence: 87%
“…Yasunaga et al (2006) investigated climatological changes in precipitation systems in the Baiu frontal zone defined as clusters of precipitation grids with 5km-NHM. They pointed out that the increase in the number of largerscale systems with the area larger than 90,000 km 2 , which corresponds to a meso-α-scale, was significant around Kyushu, while increases in the number of larger systems in other regions and that of the smaller systems were not.…”
Section: Projection Of Extreme Precipitation In the Future And Discusmentioning
confidence: 99%